Diversity and abundance of butterflies in urban areas of Bankura district, Bankura, West Bengal, India - Avisek Patra; Anirban Patra; Biplab Mandal; Anupam Ghosh (Journal of Basic and Applied Zoology)
Abstract Objective During the present study, the biodiversity profile of butterflies was assessed on the Bankura Christian College campus, a large area with a huge amount of trees, bushes, rain forest, and undisturbed areas within the urban areas of Bankura district of West Bengal, India. Methodology Present study was carried out in Bankura Christian College campus, a relatively undisturbed area in Bankura town, of West Bengal, India. The findings presented here were based on seasonal diversity of Butterflies in the college campus. The species dominance of Butterflies was numerically measured on the basis of density, relative density, abundance, relative abundance, frequency, and relative frequency. To analyze the result, single factor ANOVA was performed in between five different seasons. Seasonal variation was analysed using individual rarefaction analysis. The Jaccard similarity index was also used to conduct hierarchical classical clustering. Result A total of 47 genera and 59 species of butterflies that belongs to five families were recorded. The findings of the present study indicated a high abundance of the butterflies that belongs to Nymphalidae family comprising 13 Genera and 22 species. Conclusion In the Monsoon season, the highest number of butterflies were recorded in comparison to other seasons. Different types of ecological indices were also calculated from observed species diversity of butterflies. Individual rarefaction analysis revealed that the probability of finding the greatest specimen was in monsoon season. Hierarchical cluster analysis among seasons based on the Jaccard Similarity index using Paired group (UPGMA) shows higher similarity of butterflies in between monsoon and Fall season.